Probing the benzofuroquinolinium derivative as a potent antibacterial agent through the inhibition of FtsZ activity - Ning Sun; Li Ban; Ming Li; Zhiyuan Fang; Xiaomei Li; Wenxia Yao; Jinghui Pan; Yujing Lu; Zhihua Liu; Wing-Leung Wong (Elsevier, 2018)
A benzofuroquinolinium derivative that exhibits excellent cell division inhibitory effect was discovered through cell-based screening approach. This compound possesses potent antimicrobial activity against both Gram-positive and Gram-negative bacteria including the drug-resistant strains. In addition, this compound is able to restore MRSA susceptibility to beta-lactam antibiotics. The biochemical results suggest that the compound inhibits bacterial cell division through the disruption of GTPase activity and the polymerization of FtsZ, which is probably the mechanism of antibacterial activity. Keywords: Bacterial resistance, Antibacterial activity, FtsZ inhibitor